The effect of gradual temperature increase on oxygen consumption rates by three species of carp fishes (Cyprinidae) - Abdul-Hassan, Jabbar (University of Thi-Qar Journal of Science, 2010)
The effect of gradual temperature increase on oxygen consumption by Cyprinus carpio, Ctenopharyngodon idella and Hypophthalmichthys molitrix have been investigated. Studied fishes showed defferent responses as in the following, Cyprinus carpio > Ctenopharyngodon idella > Hypophthalmichthys molitrix > control . It is obviously clear that fishes in active way were consumed oxygen more than in resting and controls, statistical analysis showed significant correlation among the results